“Faces We Remember”: Assessing Visual Memory Depth among the Yupik of Chukotka and St. Lawrence Island - Krupnik, Igor (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
This paper addresses the issue of difference in the depth of visual memory among the Chukotka (Siberian) and St. Lawrence Island Yupik people based on several projects in heritage documentation between 1999 and 2019. Using historical photographs from museum collections and assessing how well (and how fully) Yupik Elders are able to recognize individuals and local details in various sets of historical photos roughly between 1895 and 1970, we may tentatively estimate the depth of “visual memory” and the ways it is changing. It generally fluctuates between 50 and 80–90 years due to various factors, and to the availability and memory of outstanding experts. Based on sets of historical photographs from the late 1800s, 1901, 1912, 1929, 1939, and 1967, the depth of visual memory was found to be significantly longer on St. Lawrence Island than in Chukotka Yupik communities.